Hubungan Antara Dukungan Keluarga Dengan Tingkat Kecemasan Â Pada Pasien Pre Operasi Appendictomy Di RSUD Prof. Dr. Soekandar Mojosari Kabupaten Mojokerto - Dwi w, Binarti; Suhardi, Agus (JURNAL KEPERAWATAN BINA SEHAT, 2014)
ABSTRACTFamily support are attitude, action and acceptance family towards patients who get illness. The members of family consider that a people who have full of support always ready to give helps and assistance if they needed. The anxiousness is part of human’s life that signed by fearfullness or deeply nervousness and having a continously. This research purposes to determine the relationship of family support with anxiety levels in appendictomy preoperative patients at Prof. Dr. Soekandar hospitals Mojokerto. This research is a correlational research with cross sectional approach. The population was all apendictomy preoperative patients. The sampling method was consecutive sampling. The analysis of the relationship of family support and the level of anxiety apply Spearman Rho correlation test showed a significant relationship with p = 0.004 (<α 0.05). The result showed that family support in medium category was 2 people (13%), the family support in good category was 12 people (80%), the family support in excellent category was 1 (7%), while the number and percentage of respondents who experienced in mild anxiety as much as 4 people (27%), moderate anxiety as much as 9 people (60%), and severe anxiety as much as 2 people (13%). There is no respondents in analysis who have family support in less category, and There is no respondents in analysis who have not experienced a panic and anxiety. The level of anxiety was influenced by family support, pain, ignorance, disanlement, death and anesthesia. However, the factors that affect the level of anxiety that is family support. The anxiousness would be lower if you have a good family support.Keywords: Family Support, Anxiety Level, appendictompreoperative patient.